ESP STUDENTS' ATTITUDES TOWARDS JAMBOARD: REVOLUTIONIZING SELF-INTRODUCTION IN THE DIGITAL AGE - Fitria Ningsih; Lailatul Nikmah (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
This study explores the use of Jamboard as a tool for revolutionizing self-introduction among English for Specific Purposes (ESP) students in the digital age. It examines ESP students' attitudes towards the use of Jamboard in enhancing their self-introduction skills through a mixed-method approach, using both quantitative and qualitative data collection methods. A survey questionnaire was administered to 131 ESP students. The study found that the respondents have a high perception of Jamboard's usefulness, ease of use, appearance, and interaction towards their self-introduction, with a mean score of 3.8. The technology was found to be user-friendly, easy to use, and helpful in presenting ideas and showcasing creativity. However, some students also encountered difficulties with Jamboard's usability and features. The recommendations include providing support and training for the effective use of digital tools like Jamboard and incorporating user-friendly features. These implications can inform educators and developers in promoting student engagement, creativity, and collaborative learning. Further research can explore the impact of Jamboard on student learning outcomes and their perceptions and use of digital tools in the classroom.